Direct Sensing of Nutrients via a LAT1-like Transporter in Drosophila Insulin-Producing Cells - Manière, Gérard (Cell Rep, 2016)
Dietary leucine has been suspected to play an important role in insulin release, a hormone that controls satiety and metabolism. The mechanism by which insulin-producing cells (IPCs) sense leucine and regulate insulin secretion is still poorly understood. In Drosophila, insulin-like peptides (DILP2 and DILP5) are produced by brain IPCs and are released in the hemolymph after leucine ingestion. Using Ca(2+)-imaging and ex vivo cultured larval brains, we demonstrate that IPCs can directly sense extracellular leucine levels via minidiscs (MND), a leucine transporter. MND knockdown in IPCs abolished leucine-dependent changes, including loss of DILP2 and DILP5 in IPC bodies, consistent with the idea that MND is necessary for leucine-dependent DILP release. This, in turn, leads to a strong increase in hemolymph sugar levels and reduced growth. GDH knockdown in IPCs also reduced leucine-dependent DILP release, suggesting that nutrient sensing is coupled to the glutamate dehydrogenase pathway.